Reduction of the emergency activity, during the Covid 19 Italian lockdown, what's the lesson to learn?. Issue 9 (September 2021) - Inama, M; Casaril, A; Alberti, L; Cappellari, T F; Impellizzeri, H G; Bacchion, M; Creciun, M; Moretto, G
Highlights: The analysis of the data regarding the use of emergency services during the 2020 Italian lockdown suggests a wrong use of these services in the pre-pandemic period in which many accesses were related to minor health problems. During the first 3 weeks of Italian lockdown, it was observed almost 50% less ER activity than the same period of 2019. National authorities have to develop new strategies for future pandemic response. The strengthen of the territorial health services could reduce the ER overload and the hospital's waiting list. Abstract: The COVID 19 pandemic was declared on the 9 th of March 2020. The health crisis affected the whole world with a very high and unexpected number of infected people. The situation forced the declaration of lockdown and a worldwide health system reorganization. Surprisingly, the social distancing laws caused a reduction of urgent hospital activities not COVID 19 related. The aim of this manuscript is to analyze the reasons why fewer emergencies were described during the 2020 Italian lockdown. The Data reporting urgent Emergency Room (ER) activity, during the first three weeks of the Italian lockdown (Group 1), were analyzed and compared with the same period in 2019 (Group 2). During the study period in 2020, there was a 46, 5% reduction in ER activity compared to that in 2019. Nevertheless, the hospitalization rate was higher in the 2020 then in 2019 ( p <0.05). The present data showed that almost half of the basic ER activity araised from mild health problems that could be followed by territorial health services. The strengthening of territorial medical services would allow hospitals to handle critical situations more easily and to focus activity by reducing the waiting list.